بلوچی ءُ سمیری زبان ءِ نیام ءَ لہتیں ھمگونگی: Similarities between Balochi and Sameerain Languages - Buzdar, Wahid Bakhsh (Hanken, 2009)
The Balochi language is one of the oldest languages of the Aryan region and currently .It is categorized as an Iranian language of Indo _European family .The Balochi language has a lot of similarities among the Iranian languages. The purpose of this paper is to show the etymological similarities between the Balochi and the Sumerian languages to find out the ancient relations among them. A brief history of the Sumerian languages(S) will also be discussed.